1994
DOI: 10.1111/j.1399-3054.1994.tb02960.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of properties of leaf and root glutathione reductases from spinach

Abstract: Glutathione reductase (GR; EC 1.6.4.2) was purified from spinach roots (rGR) to homogeneity in terms of SDS‐PAGE, and its properties were compared with those of the enzyme from spinach leaves (IGR). The two enzymes had similar native molecular (118000) and subunit masses (58000) and immunochemical properties, but different pH optima (ca pH 7.8 for IGR, ca pH 7.2 for rGR) and amino acid compositions. Peptide maps of two GRs showed that they differed from each other. The N‐terminal amino acid of the IGR was glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Research has also found that 0.1 M potassium phosphate is an effective extractant for plant protein (36) and that it extracts seleniferous proteins if present in nondecomposed seleniferous plant material in soil. We achieved >95% spike recovery rates by the HGAAS speciation procedure when we spiked [1 µg of each Se species (g of soil) -1 ] a nonseleniferous soil with selenate, selenite, and selenomethionine and extracted with P-buffer.…”
Section: Resultsmentioning
confidence: 99%
“…Research has also found that 0.1 M potassium phosphate is an effective extractant for plant protein (36) and that it extracts seleniferous proteins if present in nondecomposed seleniferous plant material in soil. We achieved >95% spike recovery rates by the HGAAS speciation procedure when we spiked [1 µg of each Se species (g of soil) -1 ] a nonseleniferous soil with selenate, selenite, and selenomethionine and extracted with P-buffer.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, GSSG increased by 3 per cent in L-49 and by 6 per cent in Hisar Safeda from IG stage to ripe stage indicating an increase in cellular oxidative status during ripening. Glutathione system has been reported to be involved directly in maintaining a low redox potential and thus a highly reduced intracellular environment (Tanaka et al 1994). Tomato and saskatoon fruit have also been reported to respond to the increase in oxidative stress by increasing reduced and oxidized glutathione during development (Rogiers et al 1998;Andrews et al, 2004).…”
Section: Indices Of Lipid Peroxidationmentioning
confidence: 99%
“…This is facilitated by an age-dependent increase in GRase activity (Table VI), which maintains more than 90% of cellular glutathione in the reduced form (Tanaka et al, 1994) via the NADPH-dependent reduction of GSSG (Carlberg and Mannervik, 1985). The increased synthesis of GSH during aging and its regeneration from GSSG necessitate greater consumption of ATP (Hell and Bergmann, 1988) SEED-TUBER AGE (months) and NADPH, respectively, and thus constitute increased sinks for metabolic energy in older tubers.…”
Section: Sds-pagementioning
confidence: 99%
“…Isolated mitochondria were washed with BSA-free buffer (Kumar and Knowles, 1996) and solubilized with 0.2% Triton X-100. Proteins were electroblotted to nitrocellulose as described by Luethy et al (1993), and GRase was probed with rabbit anti-spinach leaf GRase (Tanaka et al, 1994) diluted 1:1000, and alkaline phosphatase-conjugated goat secondary antibody to rabbit IgG, diluted 1:2500 with blocking buffer. GTase was probed with anti-Hyoscymus muticus GTase (Bilang and Sturm, 1995) diluted 1:lOOO with blocking buffer.…”
Section: Sds-pace and Lmmunodetectionmentioning
confidence: 99%
See 1 more Smart Citation